2016
DOI: 10.1007/s10965-016-1043-0
|View full text |Cite
|
Sign up to set email alerts
|

Effective influences of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide (EMIMTFSI) ionic liquid on the ion transport properties of micro-porous zinc-ion conducting poly (vinyl chloride) /poly (ethyl methacrylate) blend-based polymer electrolytes

Abstract: A series of new gel polymer electrolytes (GPEs) based on different concentrations of a hydrophobic ionic liquid (IL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide (EMIMTFSI) entrapped in an optimized typical composition of polymer blend-salt matrix [poly(vinyl chloride) (PVC) (30 wt%) / poly(ethyl methacrylate) (PEMA) (70 wt%) : 30 wt% zinc triflate Zn(CF 3 SO 3 ) 2 ] has been prepared using facile solution casting technique. The AC impedance analysis has revealed the occurrence of the maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Then, the authors evaluated the influence of [EMIM][TFSI] on this system and found that the weight ratio of [EMIM] [TFSI] in the electrolyte was positively correlated with the dielectric constant, amorphous phase ratio and ion conductivity. The highest ion conductivity could reach 0.11 mS cm −1 at room temperature 113,114 . Furthermore, the addition of nanosized SiO 2 in the electrolyte with an optimized composition effectively reduced T g and increased the thermal stability, electrochemical stability window (5.07 V) and ion conductivity (0.67 mS cm −1 ) at room temperature 82 .…”
Section: Polyacrylic Acid and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the authors evaluated the influence of [EMIM][TFSI] on this system and found that the weight ratio of [EMIM] [TFSI] in the electrolyte was positively correlated with the dielectric constant, amorphous phase ratio and ion conductivity. The highest ion conductivity could reach 0.11 mS cm −1 at room temperature 113,114 . Furthermore, the addition of nanosized SiO 2 in the electrolyte with an optimized composition effectively reduced T g and increased the thermal stability, electrochemical stability window (5.07 V) and ion conductivity (0.67 mS cm −1 ) at room temperature 82 .…”
Section: Polyacrylic Acid and Its Derivativesmentioning
confidence: 99%
“…The esterification of PAA triggers the coordination disruption between Zn 2+ and carboxylate radicals, paving a new route for their application in Zn 2+ transporting electrolytes. Suthanthiraraj and coworkers 82,113,114 thoroughly investigated polymer electrolytes based on poly (vinyl chloride) (PVC) and poly(ethyl methacrylate) (PEMA, Scheme 1) containing Zn(CF 3 SO 3 ) 2 as the dopant salt. First, the optimized weight ratio of the Zn salt was determined to be 30 wt% according to the thermal stability and electrochemical performance 114 .…”
Section: Polyacrylic Acid and Its Derivativesmentioning
confidence: 99%
“…On closer inspection, it may be clearly noted that the diffraction hump observed for filler-free gel polymer sample (Sn0) 15 in Figure 1(b) becomes relatively weaker, broader, as well as less significant 18 in all the gel composite complexes with the addition of ceramic nanofiller up to 3 wt%. This feature suggests the existence of possible Lewis acid–base interaction between the ether oxygen of the polymeric chain and Lewis acid sites of SnO 2.…”
Section: Resultsmentioning
confidence: 95%
“…To explore the perceptible changes in the structural characteristics of GPEs after the dispersion of nano-sized SnO 2 filler, XRD patterns of pure Zn(OTf) 2 salt, 15 filler-free gel sample Sn0, 15 pure SnO 2 nanofiller, and various specimens of PVC/PEMA-Zn(OTf) 2 -EMIMTFSI- x wt% SnO 2 (where x = 1, 2, 3, and 4, respectively) NCGPEs are displayed in Figure 1(a) and (b) and Figure 2(a) to (e). The intense diffraction peaks observed at 2 θ = 17.2°, 23.5°, 24.1°, 24.6°, and 29.8° in Figure 1(a) indicate the highly crystalline nature of Zn(OTf) 2 salt.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation